The Contribution of Absorptive Capacities to New Innovative Product Development Performance: A Conceptual Framework - Handiwibowo, Gogor Arif; Nadlifatin, Reny; Bhawika, Gita Widi; Noer, Lissa Rosdiana (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2021)
The wave of Covid-19 has forced the industry to transform so that the products produced can remain competitive in the market. Old products in the period before Covid-19 certainly no longer have the same competitive performance as today, so the industry is required to be able to develop new product innovations that can excel in the market. To be able to produce innovative new products, the industry requires sufficient knowledge. The ability of industries to be able to acquire and implement knowledge is called absorptive capacity. In various previous studies, absorptive capacity has four aspects including acquisition capacity, assimilation capacity, transformation capacity and exploitation capacity. In this article the conceptual framework for the relationship between aspects of absorptive capacity and the performance of new products is presented. We hypothesize that there are interesting correlations between aspects of absorptive capacity and new product development performance.